Pengaruh Pendidikan Karakter Terhadap Kedisiplinan Sholat Siswa Madrasah Tsamawiyah - Sulistyani, Ambar (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
This research is aimed to know how character education is implemented directly toward students, how MTs N 6 Kulon Progo students’pray discipline in academic year 2017/2018. The researcher hopes the result of this research can give motivation to all members to get good team work. This research uses quantitative approach with outdoor research. Data collection uses observation, interview and documentation method. There are 64 respondents of MTs N 6 Kulon Progo in 2017/2018 academic year. The data analysis uses simple linear regression analysis technic. The result of the research shows that : (1) Character Education in MTs N 6 Kulon Progo is in medium category. This fact can be showed from average score for character education is 83,5 whereas the score is laid in 77-88 interval; (2) Mts N 6 Kulon Progo students’ discipline is grouped in medium category too. This fact can be showed from students’ discipline score is in 79-87 interval; (3) There is positive and significant relationship between character education (X) and students’ pray discipline (Y) in MTs N 6 Kulon Progo in acadmic year 2017/2018. This result is based on product moment analysis those are rhitung 0,380 compare with rtable 5% that shows 0,254 so rhitung = 0,380 > r table = 0,254. So H0 is rejected and Ha is received, it means there is a positive and significant influence about character education toward MTs N 6 Kulon Progo Students’ Prayer discipline.